Políticas públicas de qualificação profissional no Brasil: uma análise a partir do PLANFOR e do PNQ - Tiago Antonio da Silva Jorge (2009)
This dissertation aimed to analyze the qualifications of public policies in Brazil, with the main focus on the plans for professional training that began to set as policies aimed at containment of unemployment and widening social inclusion of workers. For this analysis, a study was conducted comparing two levels of professional qualification, namely the National Plan of Labor Qualification (PLANFOR), developed and implemented in the period through Fernando Henrique Cardoso's government, and the National Plan of Qualification (PNQ), developed and implemented during Luiz Inácio Lula da Silvas government. Both plans were funded by the Fund for Support Workers (FAT). The establishment of this fund in the 1990s allowed holding an institutional apparatus for the purpose of achieving the policies supporting the unemployed and the segments of the population at social risk. The aim was to comparatively analyze the two plans of professional qualification, PNQ and PLANFOR, seeking structural changes observed with elements of effective innovation in the preparation of the PNQ in relation to PLANFOR, or if in practice, such initiatives ended representing a continuation of the first plan. The analysis presented is made based on two different axes. The first axis is related to the planning stage and it aims to establish differences in the concepts and goals of the plans and their implementation mechanisms. The second axis, related to the implementation stage, tries to compare the plans on the characterization, as well the primary care to the public and civil society participation in implementing actions of professional qualification. The development of this study was based on the methodology of documentary analysis, using secondary documentary sources. The result of this study shows that despite the present differences in relation to design and mainstream, there are strong similarities between the two plans, particularly in relation to its implementation.